Broad-spectrum non-nucleoside inhibitors of human herpesviruses - McClain, Lora (Antiviral Res, 2015)
Herpesvirus infections cause considerable morbidity and mortality through lifelong recurrent cycles of lytic and latent infection in several tissues, including the human nervous system. Acyclovir (ACV) and its prodrug, the current antivirals of choice for herpes simplex virus (HSV) and, to some extent, varicella zoster virus (VZV) infections are nucleoside analogues that inhibit viral DNA replication. Rising viral resistance and the need for more effective second-line drugs have motivated searches for additional antiviral agents, particularly non-nucleoside based agents. We evaluated the antiviral activity of five compounds with predicted lysosomotropic activity using conventional and human induced pluripotent stem cell-derived neuronal (iPSC-neurons) cultures. Their potency and toxicity were compared with ACV and the lysosomotropic agents chloroquine and bafilomycin A1. Out of five compounds tested, micromolar concentrations of 30N12, 16F19, and 4F17 showed antiviral activity comparable to ACV (50μM) during lytic herpes simplex virus type 1 (HSV-1) infections, reduced viral DNA copy number, and reduced selected HSV-1 protein levels. These compounds also inhibited the reactivation of ‘quiescent’ HSV-1 infection established in iPSC-neurons, but did not inhibit viral entry into host cells. The same compounds had greater potency than ACV against lytic VZV infection; they also inhibited replication of human cytomegalovirus. The anti-herpetic effects of these non-nucleoside agents merit further evaluation in vivo.